Nucleation and growth controlled reduced graphene oxide–supported palladium electrocatalysts for methanol oxidation reaction - Ng, Jen Chao; Tan, Chou Yong; Ong, Boon Hoong; Matsuda, Atsunori; Basirun, Wan Jefrey; Tan, Wai Kian; Ramesh, Singh; Yap, Boon Kar (SAGE Publications, 2019)
In spite of advantages of direct methanol fuel cells, low methanol oxidation reaction and fuel crossover from anode to cathode, there remains a challenge that inhibits it from being commercialized. Active electrocatalysts are in high demand to promote the methanol oxidation reaction. The methanol reached at the anode can be immediately reacted, and thus, less methanol to cross to the cathode. The performance of electrocatalysts can be significantly influenced by varying the concentration of precursor solution. Theoretically, concentrated precursor solution facilitates rapid nucleation and growth; diluted precursor solution causes slow nucleation and growth. Rapid nucleation and slow growth have positive effect on the size of electrocatalysts which plays a significant role in the catalytic performance. Upon the addition of appropriate concentration of graphene oxide, the graphene oxide was reported to have stabilizing effect towards the catalyst nanoparticles. This work synthesized reduced graphene oxide–supported palladium electrocatalysts at different concentrations (0.5, 1.0, 2.0, 3.0 and 4.0 mg mL −1 ) with fixed volume and mass ratio of reduced graphene oxide to palladium by microwave-assisted reduction method. Results showed that reduced graphene oxide–supported palladium synthesized at a concentration of 1.0 mg mL −1 gave the best methanol oxidation reactivity (405.37 mA mg −1 ) and largest electrochemical active surface area (83.57 m 2 g −1 ). © The Author(s) 2019.